Update in the clinical utilization of chemoprevention for breast cancer: a narrative review - Mansour, Razan; Abunasser, Mahmoud; Sharaf, Baha’; Abdel-Razeq, Hikmat (Frontiers in Oncology, 2025)
BackgroundBreast cancer, a leading cause of cancer-related deaths, prompts research into chemoprevention strategies. This narrative review explores risk factors, assessment tools, and summarizes the effectiveness and side effects of chemopreventive agents used for breast cancer risk reduction;MethodsPublished data from major clinical trials, meta-analyses, and data presented at major international conferences that addressed the utilization of tamoxifen, raloxifene, aromatase inhibitors (AI) and other potential drugs are reviewed. Risk assessments models utilized to assess women’s risk of getting breast cancer are discussed, too;ResultsTamoxifen, a selective estrogen receptor modulator (SERM), demonstrated efficacy in reducing breast cancer risk in postmenopausal and premenopausal women. However, it poses several worrisome adverse events. Raloxifene, another SERM, has risk-reducing benefits with a better safety profile compared to tamoxifen. AI, like anastrozole and exemestane, reduced invasive breast cancer with better side effect profile. Denosumab, a monoclonal antibody that tackles receptor activator of nuclear factor kappa B (RANK-RANKL), is promising in preventing breast cancer in healthy carriers of pathogenic BRCA1 variants. Despite their proven efficacy, chemopreventive agents are underutilized underscoring the importance of raising the awareness of health care workers and women at-risk;ConclusionChemopreventive agents present opportunities for reducing breast cancer risk. However, careful consideration of side effects and individual risk factors are crucial to enhance uptake rate. Further research is needed to compare the effectiveness of SERMs and AI in preventing breast cancer, especially in high-risk populations with pathogenic germline mutations.